In vitro techniques to assess the proficiency of skin care cosmetic formulations - Roy, Amit; Sahu, Ram Kumar; Matlam, Munglu; Deshmukh, Vinay Kumar; Dwivedi, Jaya; Jha, Arvind Kumar (Pharmacognosy Reviews)
Cosmetics comprising either natural or synthetic components are used almost regularly and universally in different forms to enhance the beauty. The utmost disclosure of human membrane to sunlight and environmental pollution results in the exhibition of free radical, that react with deoxyribonucleic acid, proteins and fatty acids, causation oxidative destruction dysfunction of the antioxidant system. In skin, the formation of reactive oxygen species leads to skin diseases, predominantly cutaneous malignancies, immunosuppression, wrinkles, aging, etc., The human organism fosters a barrier practice against the destructive action of free radicals, comprising mostly of vitamins, carotenoids and enzymes. Cosmetic products are the best option to reduce skin disorders such as hyper pigmentation, skin aging, skin wrinkling and rough skin texture, etc., Hence in this review, we conferred various in vitro methods that are used for the development of novel cosmetic formulation. There is an expanding fascinate employing in vitro techniques because they are less time consuming, more cost‑effective and lessen the participation of human volunteers.
Keywords: Aging; hyperpigmentation; in vitro methods; ultraviolet radiation; wrinkle